Mule deer: a handbook for Utah hunters and landowners - Austin, Dennis D., author; Utah State University Press, publisher (Colorado State University. Libraries, 2010)
A complete guide to the history, biology, hunting, and management of mule deer in Utah. The author, Dennis D. Austin, is a retired research scientist with more than thirty years of experience working as a wildlife biologist for the Utah Division of Wildlife Resources.
Historical Overview -- Mule Deer Biology -- Hunters, Hunting, and Harvest -- Determining Management Decisions -- Epilogue.
Keywords: Mule deer hunting -- Utah; Mule deer -- Utah; Wildlife management -- Utah